Sejarah Penilaian Hasil Belajar; - Raikhan Raikhan (JIEM: Journal of Islamic Education and Manajemen, 2020)
This paper tries to describe the problems of assessment of learning outcomes; Among the complicated problems in education are outlining the paradigm of assessment, assessment still considered a social formality of the relationship between teachers and institutions,as manager that assessment formative is only for the sake of accountability, so that the assessment process does not meet the assessment standards. Curriculum changes are also not widely understood by the community as educational dynamics, but more as mere political projects, even changes in terms in evaluation are still not understood as paradigm shifts, but are understood only to make a difference. This paper uses an explanatory descriptive approach, this paper belongs to the type of library research. Library research is research conducted by collecting data, information, and various other data contained in the literature related to the science of evaluation and its history. From this research, it shows that globally there are seven periods and this is the same as what happened in Indonesia which experienced seven changes in assessment policies and many changes were also influenced by changes in the assessment paradigm, until in the end it can be concluded that the Assessment as Learning paradigm is a paradigm that is in accordance with the concept of muhasabah in Islam.